Application of one-dimensional heat and mass transfer model of helium heated reformer coupled with HTR-10. (1st September 2023) - Zhang, Yongle; Zhang, Huang; Liu, Qianfeng; Zhou, Junbo
Highlights: Six reformer inlet parameters like the helium inlet temperature ( T 3 i n l e t ) and flow rate ( F 3 i n l e t ), process gas inlet temperature ( T 2 i n l e t ) and pressure ( P 2 i n l e t ), process gas inlet flow rate ( F 2 i n l e t ) and steam to carbon ratio ( S ) are considered. Reformer performance characteristics coupled with HTR-10 including the methane conversion rate ( X C H 4 ), carbon monoxide conversion rate ( X CO ), thermal efficiency ( η ) are analyzed. Relative errors of the methane conversion rate X C H 4 between the calculation results and the reported values are less than 5.40%. Abstract: In this paper, the heat and mass transfer characteristics of the steam methane reforming (SMR) hydrogen production performances using HTR-10 are analyzed. The hydrogen production performances includes the methane conversion rate ( X CH4 ), carbon monoxide conversion rate ( X CO ), thermal efficiency ( η ) are evaluated. In addition, the reformer inlet parameters includes the helium inlet temperature ( T 3inlet ), flow rate ( F 3inlet ), process gas inlet temperature ( T 2inlet ), pressure ( P 2inlet ), process gas inlet flow rate ( F 2inlet ) and steam to carbon ratio ( S ) are considered. Based on the reformer performance parameters (including X CH4 or η or X CO ), reformer inlet parameters (like F 2inlet, F 3inlet, T 2inlet, T 3inlet, S, P 2inlet ) and reformer length, the value of the third type of parameter are obtained using the retrieving program. Relative error of X CH4 between the calculation results and the reported values is less than 5.40%. System characteristics of the coupled system are obtained and can be helpful for the related applications.